(untitled) (Scientific journal of the Fergana State University, 2025)
This article discusses the significance of botanical terms in the terminological system, their ethnosemantic properties. By identifying the ethnocultural properties of plants, which are expressed in the history, culture, lifestyle and traditions of the people, it is possible to determine the significance of botanical terms in the life of our people. To determine this, the significance and symbolic meanings of plant-related units in rituals, folklore genres, and folk medicine were analyzed.